INTERNALIZING KALOSARA’S VALUE IN A TRADITIONAL DANCE ‘LULO’ IN THE CITY OF KENDARI, SOUTHEAST SULAWESI - Muh Subair (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Kalosara is a local wisdom which is grown in Kendari Southeast Sulawesi Indonesia, and it has been proven to strengthen peace and harmony in the tribe of Tolaki. Therefore, how to enlarge the function of Kalosara in the multicultural society, is the main discussion of this article base on the theory of multiculturalism and structural-functional in the frame of descriptive-qualitative approach, where the society interpreted as a structure that interacting each other, especially in the norms, traditions, and institutions. The analyzed of data refers to thinking narratively as a way of thinking about phenomena. Data gaining from in-depth interview, literature review, and observation indicated that the local wisdom that supports harmony in Kendari basically also presents in all ethnicities, thus strengthening of Tolakinese’s local wisdom through the internalization of Kalosara in Lulo dance can be well-received by other communities. Kalosara has effective influence in being a unifying means between the dispute parties. Therefore, to expand the access of Kalosara into more effective function, it is recommended to internalized the values of Kalosara in public activities, primarily in Lulo dance, and it is also advisable to manifest the transformation of stylistic Kalosara in the forms of jewelry or crafts, bracelets, necklaces, rings, plate plaques, and other forms that may adopt the shape of original Kalosara, simultaneously adapt its function as an integral tool. If Kalosara transforms into various shapes which is easy to carry anywhere has spread in the community, it is expected at the same time also the functions to spread to the whole society.